Deformation of ultra-soft soil - Bo Myint Win. (2008)
This study investigated the deformation behavior of ultra-soft soil upon additional load application. Various types of labortary compression tests were conducted, such as tests using small and large-scale consolidometers, hydraulic Rowe cells under different drainage conditions, Constant Rate of Loading and Constant Rate of Strain tests.